Hearing treatment for reducing cognitive decline: Design and methods of the Aging and Cognitive Health Evaluation in Elders randomized controlled trial. Issue 1 (5th October 2018) - Deal, Jennifer A.; Goman, Adele M.; Albert, Marilyn S.; Arnold, Michelle L.; Burgard, Sheila; Chisolm, Theresa; Couper, David; Glynn, Nancy W.; Gmelin, Theresa; Hayden, Kathleen M.; Mosley, Thomas; Pankow, James S.; et al.
Abstract: Introduction: Hearing impairment is highly prevalent and independently associated with cognitive decline. The Aging and Cognitive Health Evaluation in Elders study is a multicenter randomized controlled trial to determine efficacy of hearing treatment in reducing cognitive decline in older adults. Clinicaltrials.gov Identifier: NCT03243422 . Methods: Eight hundred fifty participants without dementia aged 70 to 84 years with mild‐to‐moderate hearing impairment recruited from four United States field sites and randomized 1:1 to a best‐practices hearing intervention or health education control. Primary study outcome is 3‐year change in global cognitive function. Secondary outcomes include domain‐specific cognitive decline, incident dementia, brain structural changes on magnetic resonance imaging, health‐related quality of life, physical and social function, and physical activity. Results: Trial enrollment began January 4, 2018 and is ongoing. Discussion: When completed in 2022, Aging and Cognitive Health Evaluation in Elders study should provide definitive evidence of the effect of hearing treatment versus education control on cognitive decline in community‐dwelling older adults with mild‐to‐moderate hearing impairment.